Implementasi Project Profil Pelajar Pancasila Tema Rekayasa Dan Teknologi Untuk Membangun NKRI Terhadap Pembentukan Karakter Siswa Pada SMP Muhammadiyah Lajoa Kabupaten Soppeng - Adim Isral Ayubi; Muhajir Muhajir; Suardi Suardi (Journal on Education, 2024)
Explain how the Pancasila Student Profile Project is implemented, the character that is formed through the implementation of the Pancasila Student Profile Project, and the supporting and inhibiting factors for implementing the Pancasila Student Profile Project, then follow-up efforts to overcome these factors hindering the implementation of the Pancasila Student Profile Project which has the theme of engineering and technology for building The Unitary State of the Republic of Indonesia is towards character building for students at Muhammadiyah Lajoa Middle School, Soppeng Regency. This research uses mixed research methods. Mixed methods are combining quantitative methods and qualitative methods in a study or research program, and in a critical review of reality. Mixed research methods are used to obtain a comprehensive analysis of the research problem through several stages of the research process. Qualitative data collection techniques include observation, interviews and documentation. Meanwhile, the quantitative data collection technique is in the form of a Google Form questionnaire. This research was carried out using several stages that have been carried out to achieve success in the research. The result of this research is that the implementation of the Pancasila profile project consists of several stages, namely planning, implementation, evaluation and follow-up.